PAT-3 In Vitro Growth Inhibition Activities of Natural (nCaIFN) and Recombinant (rCaIFN) Canine Interferons on Three Different Tumor-Derived Cell Lines - Bambang Pontjo Priosoeryanto; Rizki Rostantinata; Eva Harlina; Lina Noviyanti (Hemera Zoa, 2018)
Recently, from many kinds of diseases one could be counted is a tumor disease. Tumor is a degenerative disease that involved many biological pathways within the host. A tumor or neoplasm can be defined as a disturbance of growth characterized by excessive, abnormal and uncontrolled proliferation of transformed or altered cell(s) at  one or more primary points within the host, and frequently at  one or more metastatic sites (Priosoeryanto, 1994).The treatment of tumor is mostly by medical surgery which usually combined with chemotherapeutic agent(s), unfortunately the using of chemotherapeutic agent can develop a seriously side effect to the treated-patients. Biological substances like interferon (IFN) known as anti-virus agent is also one of promising candidate for treating or preventing of tumor disorders.Feline and canine squamous cell carcinoma is one of tumor type that often found in cat and dog, and mostly develop to a very aggressive disorder. The using of in vitro cell culture is a way to avoid the use of live animals on the study of tumors especially the study of antitumor agent due to can mimic the in vivo condition.  The aim of the present study is to examine the growth inhibition activity of natural and recombinant canine interferon in order to find the suitable biological substances for combating tumor disorder especially in the field of veterinary medicine and also as an information for the development of tumor treatment in the human medical side.